Genetic polymorphism and serum levels of interleukin- 38 in male patients with ankylosing spondylitis - Rehab M. Khadum; Reema Mohammed Abed (International Journal of Medical Toxicology and Legal Medicine, 2024)
Ankylosing spondylitis is a common chronic inflammatory autoimmune disorder affecting 1% of the general population. This study aimed to assess the role of the cytokine IL-38 in AS, examining serum levels, gene expression, and single nucleotide polymorphisms (SNPs). The study enrolled 200 Iraqi males, including 100 AS patients and 100 healthy controls. Baseline characteristics showed the mean age was 41.10 ±13.00 years, AS duration was 8.87 ±6.38 years, and BASFI score was 3.41 ±1.68. There was a higher proportion of married patients (74.0%) compared to non-married (26.0%), and a significant difference in heritable disease between AS and controls (p<0.001). IL-38 gene expression was significantly lower in AS (0.34-fold) than controls (1-fold, p<0.001). Genotype analysis revealed significant differences in the observed versus expected counts of rs4849146 and rs28992497 SNPs in both groups (all p<0.05). The rs4849146 heterozygous AT genotype was higher in AS versus controls (38.0% vs. 20.0%, p=0.002), while the homozygous AA genotype was lower (39% vs. 60%, p=0.003). Allele A was less frequent and T more frequent in AS (p=0.012). In AS, IL-38 expression was higher in TC and CC versus TT genotypes of rs28992497 (p=0.002). Haplotype analysis showed significant differences in A-T and T-C frequencies between groups (p<0.05). In conclusion, these findings suggest IL-38 gene expression and SNPs may play a role in the pathogenesis of AS.